Making Sense of Culture in International Business: Some Theoretical and Methodological Reflection - Michael Jakobsen; Verner Worm; Xin Li (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2016)
When analysing modes of navigating cross-cultural business communities most IB studies employ an etic approach that delineates how ethnically owned companies thrive and manoeuvre in complex cross-cultural business environments. This approach implies employing theoretical models and empirical observations that from a methodological point of view identify a local entrepreneur either as an objectified agent or as an anonymous 'other' thus pointing towards the assumption that such an approach has its roots in an ethnocentric academic tradition. This article goes beyond an etic approach and introduces an emic approach in which it is the local entrepreneurs themselves, who provide the main bulk of data on why and how they position themselves in a cross-cultural business environment the way they do. The main objective of this study is thus to show how local entrepreneurs develop business strategies so as to navigate and grow their companies in a complex cross-cultural business environments. The discussion on local entrepreneurship begins by outlining a theoretical framework for how to approach emic studies and from there proceeds towards suggesting a methodological approach that is capable of providing the empirical data that supports a theoretical framework based on an emic approach. The focus in this paper is thus to excavate how local entrepreneurs manoeuvres in a multi-cultural business context by combining both an etic and emic approach.
hdl:10398/9300
Keywords: 330; Cross-cultural business; Ethnic entrepreneurship; Etic; Emic; Culture; Semiotic; Sensmantics; Unternehmer; Ethnische Gruppe; Unternehmenskultur; Strategisches Management; Interkulturelles Management; Semiotik; Südostasien